Historical Approach and Philological Approach as Methodological Reasoning in the Study of the al-Quran (A Conceptual Study): Historical Approach dan Philological Approach sebagai Nalar Metodologis dalam Kajian Studi al-Quran (Sebuah Telaah Konseptual) - Rohman, Moh. Mujibur; Wasik, Wasik; Hidayat, Muhammad Syaiful Bahri; Yaqin, Moh. Ainul; Fadoli, Ach.; Azhari, Mohammad Nadzir (Syamilah Publisher, 2024)
As a source of Islamic law, the study of the al-Quran is an interesting study. Reactualization of understanding of the content of the al-Quran needs to be done so that the al-Quran remains pious li kulli zaman wa makan. The al-Quran as a revelation and source of law handed down from the Almighty (Allah azza wa jalla) cannot possibly be understood from a scientific aspect. Two approaches, namely the historical approach and the philological approach. It is important in understanding